Penegakan Hukum Terhadap Pelaku Tindak Pidana Perusakan Kabel Bawah Laut Di Wilayah Hukum Polres Tanjung Jabung Barat Berdasarkan Uu No. 36 Tahun 1999 Tentang Telekomunikasi (Studi Kasus: Putusan Nomor 36/Pid.Sus/2023/PNKlt) - Suzanalisa, Suzanalisa; Zachman, Nuraini; Justisia, Praja Pratama (Legalitas: Jurnal Hukum, 2023)
Underwater cables refer to all types of cables laid on the surface of the seabed, undersea cables have now developed into a Sea Cable Communication System (SKKL) thatare interconnected and mutually supportive. Underwater communication cables are cables laid under the sea to connect telecommunications between countries. The disconnection of the underwater cable communication network also occurred in the waters of the Pengabuan River, West Tanjung Jabung Regency. In this case the Tanjung Jabung Barat Resort Police, which is the jurisdiction of the incident, received a report and quickly carried out the law enforcement process, especially since this incident was the first time this had happened in the jurisdiction of the West Tanjung Jabung Police. As a result of the disconnection of the underwater cable network, it causes electromagnetic disturbances in the form of blackouts or interrupted communication networks. The purpose of this study is to understand and analyze how law enforcement is against the perpetrators of the criminal act of destroying undersea cables in the jurisdiction of the West Tanjung Jabung Police based on Law no. 36 of 1999 concerning Telecommunications (Case Study: Decision Number 36 /Pid.Sus /2023 /PN KLT), to understand and analyze the factors that become obstacles, and to understand and analyze the efforts made in overcoming existing obstacles. The research method used is empirical juridical. The results showed that in this case the Captain of the Ship, TB. DABO 103 is an element that is proven to have caused the interruption of the underwater fiber optic network in the waters of the Pengabuan Estuary, due to its negligence resulting in a violation of the provisions of Article 322 Jo Article 216 paragraph (1) of the Law of the Republic of Indonesia Number 17 of 2008 concerning Shipping whichreads"The skipper who carriesout repair activities, trial sailing, loading transfer activities at the port pool, delays, and loading and unloading of dangerous goods without the approval of the Syahbandar as referred to in Article 216 paragraph (1) shall be punished with imprisonment for a maximum of 6 (six) months or a fine 100,000,000.00 (one hundred million rupiah) at the most." For his negligence, the defendant was sentenced to imprisonment for 5 (five) months, because he was proven to have violated the provisions of Article 322 Jo Article 216 paragraph (1) of the Law of the Republic of Indonesia Number 17 of 2008 concerning Shipping, namely carrying out repair activities without the approval of Syahbandar. From the results of the research carried out, the suggestions given are that it is necessary to make ongoing appeals to captains to complete navigation tools in the form of BPI Pushidrosal Maps (Indonesian Seafarers' News) and the latest Marine Maps which serve to explain the latest situations and conditions in the waters and also which can explain the existence of the position of items under the sea including undersea cables so that similar incidents do not happen again.